Rethinking E-Learning and Face-to-Face Learning for Sustainable Blended Higher Education: A Commentary - Verawati, Ni Nyoman Sri Putu; Wahyudi, Wahyudi (LITPAM, 2026)
This commentary rethinks the relationship between e-learning and face-to-face learning in higher education after the COVID-19 pandemic. Drawing on students’ preferences and behaviors, it argues that the future of higher education should not be framed as a choice between digital and in-person instruction. E-learning offers flexibility, accessibility, convenience, and continuity, but these benefits are insufficient when online learning lacks interaction, social presence, practical experience, and pedagogical depth. Face-to-face learning remains important because it supports direct communication, academic belonging, mentoring, and hands-on activities. However, returning fully to traditional classroom routines would ignore the valuable lessons gained from digital learning. This commentary proposes sustainable blended higher education as a more balanced direction, where online and face-to-face components are intentionally designed according to learning objectives. Universities should build human-centered, inclusive, and pedagogically coherent blended systems that preserve flexibility while strengthening interaction, engagement, equity, and educational quality across diverse student contexts and institutional conditions.